Redesain UI dan UX Website Suara Garut: Pendekatan Design Thinking Untuk Meningkatkan Kenyamanan Akses Berita Lokal - Fauzan Romi Juliansyah; Ridwan Setiawan (Institut Teknologi Garut, 2026)
This study aims to redesign the User Interface and User Experience on the Suara Garut website using the Design Thinking approach. The background of this study is the challenges faced by the existing website, such as unattractive visual design, confusing navigation, and suboptimal information structure, which impact user comfort. The design process was carried out through five systematic stages, namely Empathize, Define, Ideate, Prototype, and Test. Data collection was conducted through interviews with the management and distribution of questionnaires to 50 users to identify their needs. The design solution was realized in the form of an interactive high-fidelity prototype using Figma. The evaluation was conducted using the System Usability Scale (SUS), involving 15 respondents. The test results showed an average score of 83.4, which falls into the “Excellent” category with an “Acceptable” level of acceptance, indicating that the interface design was very well received. This study successfully produced a design that addresses the real needs of Suara Garut website users.